EPIDEMIOLOGY OF MATERNAL MORTALITY AND POOR PERINATAL OUTCOMES IN DIFFERENT REGIONS OF SUDAN - M. Elhassan, Elhassan; A. Hassan, Ahmed; D. Haggaz, Abd Elrahium; A. Ali, Abdel Aziem; Adam, Ishag (Gezira Journal of Health Sciences, 2010)
Background: Both maternal mortality and poor perinatal outcomes (mainly; low birth weight, stillbirth and perinatal mortality) are health as well as obstetrics indicators. Thus, there is an urgent need to investigate epidemiology of maternal mortality and poor perinatal outcomes in the different regions of Sudan. Objectives: To investigate the epidemiology of maternal mortality and poor perinatal outcomes in the different regions of Sudan. Methods: Various cross- sectional, case -control, and Cohort studies were conducted during the last 7 years. Results:   Maternal mortality was ranged 442 (146/33034)-640 (63/9841) / 100000 birth in the different regions of Sudan, most of these were due to communicable diseases. Low birth weight was reported in 15.3% (80/524), 12.5% (260/2076), 12.6% (97/1224), 14.9% (64/430) 12.6% in New Halfa, Khartoum, Medani and Elfashir, respectively. Anaemia was risk factors for low birth weight in Elfashir and in Medani; it was risk factor for fetal anaemia in New Halfa and risk factor for stillbirth in Kassala. There were 21 (206/9841), 29 (981/34015), 35(46/1293)/ 1000 stillbirths and 33(44/1342)/1000 in Elfashir, Medani, Khartoum respectively and Kassala, respectively. There was 9.2% (46/500) perinatal death in New Halfa. Conclusion: More effort should be paid to reduce the high maternal and perinatal mortality. More care should be toward nutrition, malaria prevention and other communicable diseases